Clinical efficacy and tendon integrity of patients with subscapularis tear by the technique of arthroscopic single external row repair - Zheng, Weipeng; Weng, Rui; Wu, Xiaohang; Liu, Zhijun; Liao, Zhihao; Chen, Sheng; Zheng, Suming; Yi, Zhiyong; Huang, Xudong; Wei, Hewei (Frontiers in Medicine, 2023)
Background: With the development of arthroscopic technology and equipment, arthroscopy can effectively repair the tear of subscapular muscle. However, it is difficult to expose the subscapular muscle and operate it under the microscope. In this study, the SwiveLock® C external row anchor under arthroscopy was applied to repair the tear of the subscapular muscle in a single row which is relatively easy to operate with reliable suture and fixation, and its efficacy was evaluated.Purpose: To assess the clinical efficacy and the tendon integrity of patients who had subscapularis tears by adopting the single row repair technique with applying SwiveLock® C external row anchor.Methods: Patients who had subscapular muscle tear either with or without retraction were included, and their follow-up time was at least 1 year. The degree of tendon injury was examined by magnetic resonance imaging (MRI) and confirmed by arthroscopy. The tendon was repaired in arthroscopic manner by utilizing the single row technique at the medial margin of lesser tuberosity. One double-loaded suture SwiveLock® C anchor was applied to achieve a strong fixation between the footprint and tendon. All patients were evaluated for shoulder joint range of motion, pain visual simulation score, American Shoulder and Elbow Surgeon score and Constant score before operation, 3 months after operation and at least 1 year after operation.Results: 110 patients were included, including 31 males and 79 females, with an average age of 68.28 ± 8.73 years. Arthroscopic repair of subscapular tendon with SwiveLock® C external anchor can effectively improve the range of motion of the shoulder joint. At the last follow-up,